A Study to Assess the Effectiveness of Structured Teaching Programme on Knowledge Regarding Common Pediatric Emergencies and Its First Aid Management Among Mothers of Under Five Children in Srm General Hospital - S. Tamilselvi, S. Tamilselvi; Shaji J C, Helen; Prakash.R, Sam; Shakthi.V, Shakthi.V; Sindhiya.V, Sindhiya.V (Journal of Neonatal Surgery, 2025)
First aid is a crucial intervention in managing pediatric emergencies and can play a vital role in preventing complications and fatalities. This study assesses the effectiveness of a structured teaching program aimed at improving the knowledge of mothers of under-five children regarding common pediatric emergencies and their first aid management at SRM General Hospital. A pre-experimental research approach was utilized, where 40 mothers participated in pretest and posttest assessments. The findings demonstrated a significant enhancement in knowledge post- intervention, underscoring the importance of structured teaching programs in maternal education. These programs equip mothers with the necessary skills to handle pediatric emergencies efficiently, thereby improving child health outcomes.